Local Method of Approximate Particular Solutions for Two-Dimensional Unsteady Incompressible Flow - Muzik, Juraj; Kais, Ladislav; Bulko, Roman (Communications - Scientific letters of the University of Zilina, 2016)
A meshless local method of approximated particular solutions (LMAPS) is used to analyze incompressible fluid flow in a two dimensionalcavity. The method solves the incompressible Navier-Stokes equations in terms of theprimitive variables using the fractional step scheme. The basic equations are derived via interpolation using integrated multiquadrics radial basis functions. Lid-driven cavity benchmark case for various Reynolds numbers is presented in the article. The procedure produces stable solutions with results comparable to those in literature.